I21 Studying the effect of cariprazine in induced neurons directly reprogrammed from Huntington's disease patient's fibroblasts. (12th September 2022) - Abbas, Anna; Danics, Lea; Kis, Balázs; Göblös, Anikó; Barker, Roger A; Veréb, Zoltán L; Jakobsson, Johan; Kemény, Lajos; Molnár, Judit Mária; Pircs, Karolina
Abstract : Background: Huntington disease (HD) is an uncurable autosomal dominant progressive neurodegenerative disorder. The role of the dopaminergic system in the development of HD symptoms is crucial, as the central dopaminergic pathways are overactivated in HD. The dopaminergic overactivity can be reduced by several drugs. However, their effectivity on psychiatric symptoms is limited. Moreover, the treatment of apathy and cognitive symptoms still remains challenging in HD. Cariprazine, a third-generation antipsychotic is acting as a dopamine D3 and D2 receptor agonist. Previous results shown positive effect in HD patients after cariprazine treatment. Clinical studies indicated positive effects in early stage of HD patients after cariprazine treatment in some psychiatric symptoms such as depressed mood, apathy and cognitive function in patients. Moreover, cariprazine also improved dopamine imbalance in the prefrontal cortex. Aims: In this project we aim to study the effect of cariprazine in a novel in vitro model system of HD using donor-derived aged induced neurons. Our goal is to understand the putative beneficial effects of cariprazine in HD patients and to better understand its mechanism of action by focusing on autophagy. Methods: Using reverse translational strategy, we use cariprazine treatment in induced neurons directly reprogrammed from 5 ctrl, 5 HD drug naive and 5 cariprazine treated HD patients' fibroblasts. For detection we use immunocytochemistry (ICC) followed by high-content automated microscopy (HCS). Expected Result: We suppose that the described abnormal neurit morphology and the neurit-specific impairment of subcellular autophagy are positively altered following cariprazine treatment.